2011
DOI: 10.3102/0162373711413814
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Distance Education across Virginia's Community Colleges: Evidence from Introductory College-Level Math and English Courses

Abstract: Although online learning is rapidly expanding in the community college setting, there is little evidence regarding its effectiveness among community college students. In the current study, the authors used a statewide administrative data set to estimate the effects oftaking one's first collegelevel math or English course online rather than face to face, in terms ofboth course retention and course performance. Several empirical strategies were used to minimize the effects ofstudent selfselection, including mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
160
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(173 citation statements)
references
References 21 publications
9
160
1
3
Order By: Relevance
“…Students in online university courses have higher attrition rates compared to face-to-face courses (Carr, 2000;Xu, 2014;Xu, 2011). Because there is no cost to enroll in a MOOC and registration is a simple process, completion rates for MOOCs are low compared to traditional online and face-toface courses.…”
Section: Introductionmentioning
confidence: 99%
“…Students in online university courses have higher attrition rates compared to face-to-face courses (Carr, 2000;Xu, 2014;Xu, 2011). Because there is no cost to enroll in a MOOC and registration is a simple process, completion rates for MOOCs are low compared to traditional online and face-toface courses.…”
Section: Introductionmentioning
confidence: 99%
“…Studies found that students who took online course at community colleges had a lower performance on average. Xu and Jaggars (2011;2013; and Hart, Friedmann and Hill (2015) conducted separate studies in community colleges in Virginia and California and they found similar results that students enrolled in online courses performed not well as compared to their peers in face-to-face courses. On the other hand, there are also studies at four-year colleges reporting no or few differences in student performance in the two different delivery formats.…”
Section: Assessment Of Online Course and Student Outcomesmentioning
confidence: 86%
“…Xu and Jaggars present evidence that online courses negatively impact the outcomes in maths and English courses 80 . The same authors returned to the issue in 2013 in Washington State community colleges and concluded in a further study that specifically analysed the influence of online learning on course grade and student persistence.…”
Section: The Us Community College Sector -A Possible Model For Strongmentioning
confidence: 99%